2014
DOI: 10.1111/hsc.12154
|View full text |Cite
|
Sign up to set email alerts
|

The boundaries of care work: a comparative study of professionals and volunteers in Denmark and Australia

Abstract: This paper explores the manner in which two hospices--one located in Denmark and one in Australia--negotiate and determine the boundaries of volunteer workers vis-à-vis paid staff. A comparative case study approach was used to juxtapose organisations with similar activity fields located in different welfare state systems, i.e. a social democratic welfare state and a liberal welfare state. This study involved non-participant observation of volunteers at work and unstructured interviews with volunteers, staff an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 24 publications
2
18
0
2
Order By: Relevance
“…The collaboration between front-line workers and volunteers is somewhat understudied, both in research on volunteering (Wilson, 2012), and in the sociology of professions (Saks and Van Bochove, forthcoming). Various scholars have explored the boundaries between volunteering and paid work (e.g., Hoad, 2002; Merrell, 2000; Overgaard, 2015; Van Bochove et al , 2016). Their studies showed that these boundaries were clear regarding care provision, such as washing or dressing clients in a nursing home, but that there were also ‘grey areas’ in which it was unclear whether a volunteer was allowed to take over a certain task or not.…”
Section: Theorising Professionalism Under Conditions Of Volunteer Resmentioning
confidence: 99%
See 1 more Smart Citation
“…The collaboration between front-line workers and volunteers is somewhat understudied, both in research on volunteering (Wilson, 2012), and in the sociology of professions (Saks and Van Bochove, forthcoming). Various scholars have explored the boundaries between volunteering and paid work (e.g., Hoad, 2002; Merrell, 2000; Overgaard, 2015; Van Bochove et al , 2016). Their studies showed that these boundaries were clear regarding care provision, such as washing or dressing clients in a nursing home, but that there were also ‘grey areas’ in which it was unclear whether a volunteer was allowed to take over a certain task or not.…”
Section: Theorising Professionalism Under Conditions Of Volunteer Resmentioning
confidence: 99%
“…Unpaid workers such as volunteers are increasingly not only expected to provide a little ‘extra’ on top of professional work (Handy and Srinivasan, 2005), but also to take over parts of professional work (Baines, 2004; Van Bochove et al , 2016; Hoad, 2002). Although cross-national (Overgaard, 2015) and cross-sector (Van Bochove et al , 2016) differences exist, a trend of ‘volunteer responsibilisation’ for such tasks is observed in a range of countries, including Germany and Italy (Komp et al , 2013; Muehlebach, 2012), Scandinavian countries (Lorentzen and Henriksen, 2014), the UK (Hardill and Baines, 2011), the Netherlands (Verhoeven and Tonkens, 2013), Canada (Baines, 2004; Elson, 2009) and Australia (Johansson et al , 2012). Much has been written on the potential threats of New Public Management (NPM) strategies (Duyvendak et al , 2006; Evetts, 2011; Harington and Bedoe, 2014; Noordegraaf, 2006; Sirotkina and van Ewijk, 2009) and ‘proto-professionalisation’ of clients (Dent, 2006; De Swaan, 1988) for professionalism.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, professional rhetoric and talk can be strategically used by actors “to influence the direction and pace of change, but also to legitimate or delegitimate the acceptance of a particular program of change” (Suddaby & Viale, 2011, p. 434). Given the shifting boundaries between paid and unpaid staff in many public service organizations across welfare states (Eliasoph, 2011; Overgaard, 2015; Van Bochove et al, 2018), it is particularly relevant to research how organizational change in such organizations is promoted via the enactment of various professionalization strategies.…”
Section: Institutional Change and The Enactment Of Institutional Workmentioning
confidence: 99%
“…3. The presence of tensions between volunteers and employees is a known and identified issue in several countries and organizational environments (Bittschi, Pennerstorfer, & Schneider, 2015;Overgaard, 2014). Most often, volunteers are perceived by employees as a threat to the safety of their job or their responsibilities, which can be taken over by volunteers.…”
Section: Directions Of Changementioning
confidence: 99%